Croswell Bowen : a writer's life, a daughter's portrait - Bowen, Betsy Connor, 1944- (Potomac Books, an imprint of the University of Nebraska Press, 2014)
A daughter''s quest to understand her father through his work at the intersections of journalism, democracy, and liberalism during the WW II, the McCarthy era, presidency of JFK, and the Vietnam War.